Psilocybin Induces Aberrant Prediction Error Processing of Tactile Mismatch Responses—A Simultaneous EEG–FMRI Study. (13th July 2021) - Duerler, Patricia; Brem, Silvia; Fraga-González, Gorka; Neef, Tiffany; Allen, Micah; Zeidman, Peter; Stämpfli, Philipp; Vollenweider, Franz X; Preller, Katrin H
Abstract: As source of sensory information, the body provides a sense of agency and self/non-self-discrimination. The integration of bodily states and sensory inputs with prior beliefs has been linked to the generation of bodily self-consciousness. The ability to detect surprising tactile stimuli is essential for the survival of an organism and for the formation of mental body representations. Despite the relevance for a variety of psychiatric disorders characterized by altered body and self-perception, the neurobiology of these processes is poorly understood. We therefore investigated the effect of psilocybin (Psi), known to induce alterations in self-experience, on tactile mismatch responses by combining pharmacological manipulations with simultaneous electroencephalography–functional magnetic resonance imaging (EEG–fMRI) recording. Psi reduced activity in response to tactile surprising stimuli in frontal regions, the visual cortex, and the cerebellum. Furthermore, Psi reduced tactile mismatch negativity EEG responses at frontal electrodes, associated with alterations of body- and self-experience. This study provides first evidence that Psi alters the integration of tactile sensory inputs through aberrant prediction error processing and highlights the importance of the 5-HT2A system in tactile deviancy processing as well as in the integration of bodily and self-related stimuli. These findings may have important implications for the treatment of psychiatric disorders characterized by aberrant bodily self-awareness.